Effects of using Visual Aids on the 9th EFL graders' reading comprehension at a secondary school in Kien Giang province - Phạm Thị Chương (Trường Đại học Trà Vinh, 2024)
The research was carried out to fulfil two aims: The main objective of this study is to find out how the use of visual aids affects EFL 9th graders’ reading comprehension and another aim is to investigate students' attitudes towards the use of visual aids in their reading comprehension lessons.